ANALISIS FIQIH MUAMALAH KONTEMPORER TERHADAP TREN BANK EMAS DIGITAL STUDI PADA LAYANAN BANK EMAS DI APLIKASI BYOND BY BSI - ARIFAH DWI AGUSTINA; Muhammad Yazid (LPPM STAI Muhammadiyah Probolinggo, 2026)
The digital Gold Bank service from Bank Syariah Indonesia (BSI) presents a sharia-compliant gold investment innovation that makes it easier for people to access, buy, sell, and transfer gold digitally through the BSI Mobile application. This product is designed in accordance with sharia principles, using clear contracts such as murabahah and wadiah, and is supervised by the Financial Services Authority (OJK) and the Sharia Supervisory Board (DPS) to ensure the halal status and certainty of gold ownership. The use of digital technology supports increased sharia financial literacy and inclusion, offering easy access, security, and efficiency in gold transactions without the need to store physical gold directly. While offering potential stability and investment benefits for the Muslim community, this service faces challenges such as annual administration fees, taxes on gold transactions, and the need for further education regarding financial technology. Overall, BSI Gold Bank is a modern solution that is relevant to the contemporary Islamic economic and financial context, while also supporting the achievement of the maqasid sharia objectives of wealth preservation and economic justice.